BISRULA (Biskuit Rumput Laut) : Inovasi Terbaru Pemasaran Rumput Laut Dalam Upaya Pencegahan Hipertensi pada Ibu Hamil di Kota Makassar - Anis Ammar Mihdar; Andi Moh. Roem Askari; Muh. Haedar; Yasmin Syauki (Hasanuddin University, 2017)
Preeclampsia is a major cause of maternal and child morbidity and mortality worldwide, especially in developing countries such as Indonesia. Pregnant women with insufficient iodine can trigger hypothyroidism and further preeclampsia. Seaweed contains essential Iodine for pregnant women and can be an alternative prevention of preeclampsia in pregnant women. This study aims to examine the effectiveness of the management and development of seaweed biscuits as the potential food to prevent hypertension in pregnant women. The current study was experimental study with pretest - posttest control group design. A total 14 samples were selected by purposive sampling method from all pregnant women in Tamalanrea sub-district as the population. The results showed that the effectiveness of management and provision of BISRULA has not been significant to reduce the blood pressure of pregnant women (p>0.05). This is due to only a few numbers of samples obtained in this study. It was difficult to find the appropriate sample based on the criteria and also because of the short duration of research so that it is difficult to prove the effectiveness of BISRULA. Furthermore, the measuring tool used has not detailed to examine the changes occurring in samples. Therefore, these findings can be suggestions for conducting further research in the future.Keywords: preeclampsia, iodine deficiency, hypertension, seawed